1986
DOI: 10.1016/s0735-1097(86)80150-4
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide assessment of left ventricular diastolic filling in diabetes mellitus with and without cardiac autonomic neuropathy

Abstract: Indexes of left ventricular diastolic filling were measured by radionuclide ventriculography in 28 patients with insulin-dependent diabetes mellitus without evidence of ischemic heart disease. Six patients (21%) had abnormal diastolic filling and differed from diabetic patients with normal filling in their greater severity of cardiac autonomic neuropathy, assessed by noninvasive means, and their lower plasma norepinephrine levels in the supine (131.1 +/- 24.7 versus 356.2 +/- 58.4 pg/ml, p less than 0.01) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
49
1
5

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(66 citation statements)
references
References 31 publications
11
49
1
5
Order By: Relevance
“…Because this study was intended to address the benefit of ARI treatment in patients without overt CAD, we excluded subjects with evidence of ischemia based on myocardial perfusion imaging, as has been done in prior studies (6,10,(15)(16)(17). Although myocardial perfusion imaging detects significant CAD and has prognostic importance (45), it does not entirely exclude the presence of mild CAD, microvascular ischemia, or endothelial dysfunction (46).…”
Section: Radionuclide Ventriculographymentioning
confidence: 99%
See 2 more Smart Citations
“…Because this study was intended to address the benefit of ARI treatment in patients without overt CAD, we excluded subjects with evidence of ischemia based on myocardial perfusion imaging, as has been done in prior studies (6,10,(15)(16)(17). Although myocardial perfusion imaging detects significant CAD and has prognostic importance (45), it does not entirely exclude the presence of mild CAD, microvascular ischemia, or endothelial dysfunction (46).…”
Section: Radionuclide Ventriculographymentioning
confidence: 99%
“…Patients with diabetes have abnormalities in left ventricular (LV) function, including parameters of diastolic filling (6,7), LV systolic strain (8), and augmentation of LV ejection fraction (LVEF) with exercise (9 -11). Cardiac dysfunction may result from abnormalities in intracellular calcium regulation, heart metabolism, contractile proteins, or remodeling of the extracellular matrix (1,12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered the most important manifestation of diabetic autonomic neuropathy [3], because it is associated with life-threatening clinical entities such as silent myocardial ischemia [4], coronary artery disease [5], peri-operative cardiovascular instability [6], QT segment prolongation [7], and stroke [8], resulting in increased mortality [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on Type 1 diabetic patients without ischemic heart disease showed that severe CAN was correlated with abnormal cardiac diastolic filling [164]. Higher levels of ventricular fibrillation are reported in diabetic patients, suggesting high sympathetic activity in diabetes [165].…”
Section: Cardiac Autonomic Neuropathy (Can)mentioning
confidence: 99%